Journal Of Indonesia Economy & Bisnis = Jurnal Ekonomi & Bisnis Indonesia - Wendy (Faculty of Economic & Business Universitas Gadjah Mada, 2012)
NO. Penulis ---- Judul Artikel ---- Halaman 1. Wendy dan Marwan Asri ---- Psychological Biases in Investment Decisions : An Experimental Study of Myopic Behavior in Developing Capital Markets ---- 143-158 2. Hasan dan Eduardus Tandelilin ---- Banking Market Discipline in Indonesia an Empirical Test on Conventional and Islamic Bank ---- 159-173 3. Keumala Hayati dan Indra Caniago ---- Model of Poor Society Empowerment Through Optimizing the Potential of Zakat : A Case Study in Lampung Province ---- 174-191 4. Sumiyana dan Raj,at Febrianto ---- Related Parties’ Transaction and Earnings Management : A Case in Indonesia ---- 192-209 5. Rayenda Brahmana, Chee-Wooi Hooy and Zamri Ahmad ---- Bad News Announcement on Investor’s Monday Irrationality : Insight From Malaysia ---- 210-223 6. Budi Santoso ---- The Influences of Javanese Culture in Power of Making Decisions in Indonesian Universities : Case Studies in MM Programmes ---- 224-241 7. Willy Abdillah, Jogiyanto HM dan Hani Handoko ---- Motivation and Consequence of Individual’s Involvement in Social Network Sites : A Study of Social Computing of Inter Collectivist-Individualist Cultural Value ---- 242-270 8. Hunik Sri Runing S. and Malik Cahyadin ---- The Moderation Effect of Commitment to Supervisor and Internet Expertise on Work Stressor and Employee Cyberloafing : A Study on Employee of Local Government of Surakarta ---- 271-284